Data warehouse Implementation on Denpasar City Online Community Complaints System - I Putu Ari Putra Wijaya; Wahyudin Wahyudin; Made Mataram (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2017)
Department of Communications and Informatics, appointed as Executor of Handling Complaint Society in Denpasar City. Over time and more complex data complaints that come in so complicate the data analysis, to overcome the data it is necessary implementation of data warehouse. The method used is Snowflake Schema, this method is chosen because this method is the development of star schema where each dimension table can have sub-table dimension. It aims to minimize data overload. From the results of the implementation in get the conclusion that by implementing data warehouse can facilitate the user in view report in accordance with the desired from summary to detail.